Interfacial solar evaporation for water production: from structure design to reliable performance. Issue 2 (29th January 2020) - Bai, Haoyu; Zhao, Tianhong; Cao, Moyuan
Abstract : Interfacial solar evaporation has emerged as a convenient and efficient strategy for harvesting solar energy, and shows promising application in the fields of water purification, desalination, and atmospheric water harvesting. Abstract : Interfacial solar evaporation has emerged as a convenient and efficient strategy for harvesting solar energy, and shows promising application in the fields of water purification, desalination, and atmospheric water harvesting. During the last decade, advanced photothermal materials as well as innovative structural design for preparing high-performance solar evaporators have been widely reported. In this review article, we firstly conclude the basic principle of design and fabrication of current solar evaporators. In the second section, we aim to propose some existing issues that hamper the reliable performance of solar evaporation systems, including the floating stability, anti-scaling ability, heat management, integrated system design, etc. Finally, the prospect of future development of such solar evaporation systems is proposed. This review article is focused on the key problems for real-world application of solar steam generation at air/water interfaces, and could stimulate new thinking about evaporator design and serve as an instruction for future investigations.